2016
DOI: 10.1080/10942912.2016.1218893
|View full text |Cite
|
Sign up to set email alerts
|

Functional components, antidiabetic, anti-Alzheimer’s disease, and antioxidant activities of Salvia syriaca L.

Abstract: View related articles View Crossmark data Citing articles: 24 View citing articles Functional components, antidiabetic, anti-Alzheimer's disease, and antioxidant activities of Salvia syriaca L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 42 publications
8
37
1
Order By: Relevance
“…Though, the choice of method and the solvent used for extraction plays a vital role in the determination of the antioxidant potential of the prepared extracts. In similar studies, it was found that the antioxidant potential of extracts depends upon the total phenolic and flavonoid contents [22,32], that is in accordance with our study. Thus, in this study, the higher amount of total phenolic and flavonoid content may be responsible for the potent antioxidant potential.…”
Section: Antioxidant Potentialsupporting
confidence: 92%
“…Though, the choice of method and the solvent used for extraction plays a vital role in the determination of the antioxidant potential of the prepared extracts. In similar studies, it was found that the antioxidant potential of extracts depends upon the total phenolic and flavonoid contents [22,32], that is in accordance with our study. Thus, in this study, the higher amount of total phenolic and flavonoid content may be responsible for the potent antioxidant potential.…”
Section: Antioxidant Potentialsupporting
confidence: 92%
“…Both essential oils exhibited the same anti‐enzymatic activity, which was approximately four times lower than that of acarbose ( P < 0.05). The antidiabetic activities of essential oils have been documented from plants including Origanum vulgare , Artemisia herba and Ocimum basilicum , Coleus aromaticus , Salvia syriaca , Afromomum melegueta and Afromomum danieli , and Syzygium aromaticum and Cuminum cyminum. The antidiabetic activities of carvacrol, thymol, and linalool have been confirmed by in vitro and in vivo studies …”
Section: Resultsmentioning
confidence: 99%
“…Taking into account that the determined dominant phenolics express great bioactivity, that it is confirmed that they prevent several diseases such as cancer, cardiovascular ailments, neurodegenerative diseases, obesity, and infectious disease, and that the juniper is already introduced into diet, the juniper-fortified food products could be considered as potent nutraceuticals in general health promotion. [21,22,23] Furthermore, a considerable content of catechin, rutin, and quercetin indicates J. excelsa as a natural preservative for stopping food spoilage by bacteria and fungi or LP during preparation, storage, and distribution. [1,24,25] .…”
Section: Resultsmentioning
confidence: 99%